Yesus sebagai Juru Selamat Dunia dalam Dialog dengan Perempuan Samaria: Kajian Kristologis Yohanes 4:1-42 - Yustinus, Yustinus (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2025)
Jesus, who deliberately crossed the region of Samaria—an area avoided by the Jews—to meet a Samaritan woman near Jacob’s well in the town of Sychar, raised many questions about the purpose and theological significance of His action. This study investigated the Christological meaning of Jesus’ self-revelation as the Messiah and Savior of the world in the dialogue with the Samaritan woman in John 4:1–42. Using a qualitative method through literature study and textual exegesis, the research found that Jesus’ intentional passage through Samaria, an area traditionally avoided by Jews, carried divine intent as part of God's universal plan of salvation. This act by Jesus reflected the early stage of salvation for non-Jewish nations and served as an example for the disciples prior to receiving His message in Acts 1:8. This study affirmed the importance of an inclusive and missiological Christology in responding to a socially fragmented reality marked by ethnic, gender, and religious divisions.AbstrakYesus yang sengaja melintasi wilayah Samaria yang dihindari orang Yahudi, untuk menjumpai perempuan Samaria dekat sumur Yakub, di kota Sikhar, menimbulkan banyak pertanyaan tentang tujuan dan makna teologis tindakan Yesus. Penelitian ini menyelidiki makna Kristologis dari pewahyuan diri Yesus sebagai Mesias dan Juru Selamat dunia dalam peristiwa dialog dengan perempuan Samaria di Yohanes 4:1-42. Pemakaian metode kualitatif melalui tahapan studi literatur dan eksegesis teks, menemukan bahwa tindakan Yesus yang sengaja melintasi wilayah Samaria, wilayah yang secara tradisional dihindari oleh orang Yahudi, mengandung intensi ilahi sebagai bagian dari agenda keselamatan Allah yang bersifat universal. Tindakan Yesus ini merupakan cerminan awal dari misi keselamatan bagi bangsa-bangsa non Yahudi dan sekaligus menjadi teladan bagi para murid sebelum menerima pesan Yesus dalam Kisah Para Rasul 1:8. Penelitian ini menegaskan pentingnya Kristologi yang inklusif dan misiologi dalam menghadapi realitas sosial yang terfragmentasi secara etnis, gender, dan agama.